2021
DOI: 10.4014/jmb.2104.04041
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Reactive Red 141 by Paenibacillus terrigena KKW2-005 and Examination of Product Toxicity

Abstract: Azo dyes play an important role as coloring agents in the textile, food, and pharmaceutical industries. They offer straightforward and cost-effective synthesis, stability, and a wider variety of colors than natural dyes [1][2][3]. Azo dyes absorb light in the visible spectrum due to their chemical structures, which are characterized by one or more azo groups (R1-N=N-R2) [4]. The azo can be substituted with benzene or naphthalene groups; they can contain many different substituents, such as chloro (-Cl), methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Telke et al [ 50 ] reported naphthalene diazonium, 1, 3, 5-triazine 2, 4-diol, and p-dinitrobenzene as degradation products of RR 141, while Aniline and 1,3,5-triazine were reported by Dias et al [ 51 ] as degradation products of RR 239. Similarly, Sompark et al [ 52 ] performed GC-Ms analysis to propose RR 141 transformation pathways and reported four fragmentation patterns as 3-diazenylnaphthalene-1,5-disulfonate, sodium naphthalene-2-sufonate, 4-chloro-1,3,5-triazin-2-amine and N1-(1,3,5-triazin-2-yl) benzene-1, 4-diamine. Furthermore, Carliell et al [ 53 ] proposed the transformation of RR 141 into 1, 3, 5-triazine, 2, 4, 6-trioxo, p -diaminobenzene, 2-aminonaphthalene-1,5-disulfonic acid and 1,7-diamino-8-naphthol-3,6-disulfonic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Telke et al [ 50 ] reported naphthalene diazonium, 1, 3, 5-triazine 2, 4-diol, and p-dinitrobenzene as degradation products of RR 141, while Aniline and 1,3,5-triazine were reported by Dias et al [ 51 ] as degradation products of RR 239. Similarly, Sompark et al [ 52 ] performed GC-Ms analysis to propose RR 141 transformation pathways and reported four fragmentation patterns as 3-diazenylnaphthalene-1,5-disulfonate, sodium naphthalene-2-sufonate, 4-chloro-1,3,5-triazin-2-amine and N1-(1,3,5-triazin-2-yl) benzene-1, 4-diamine. Furthermore, Carliell et al [ 53 ] proposed the transformation of RR 141 into 1, 3, 5-triazine, 2, 4, 6-trioxo, p -diaminobenzene, 2-aminonaphthalene-1,5-disulfonic acid and 1,7-diamino-8-naphthol-3,6-disulfonic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Because of this, UV-Vis responses cannot be directly compared with responses from techniques such as HPLC; they must complement each other. Therefore, UV-Vis analysis can be used to assess discoloration and HPLC to investigate the mechanisms of discoloration and the removal percentage [65].…”
Section: Phytotoxicity Assaymentioning
confidence: 99%
“…Bacteria adapt well to various types of stresses, including hazardous wastes and harsh living conditions, which are considered positive features for the enhancement of many contaminated environments [ 11 ]. In particular, the activity of bacterial enzyme systems contributes to the biotransformation of toxicants into non-toxic metabolites through metabolic mechanisms [ 12 ]. Several types of enzymes have reportedly been found to be effective molecular weapons for participating in dye degradation, including oxidative enzymes (polyphenol oxidase (PPO), manganese peroxidase (MnP), lignin peroxidase (LiP), laccase (Lac), tyrosinase (Tyr), and N-demethylase), reductive enzymes (azoreductases), and immobilized enzymes (oxidoreductases)) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous bacterial strains have been investigated as potential candidates for functional bioremediation agents to decolorize and mineralize dyes that contaminate soil and wastewater. In a previous study, a bacterium Paenibacillus terrigena KKW2-005—isolated from dye-contaminated soil—was identified and its ability was determined to be capable of decolorizing 96.45% of the azo dye Reactive Red 141 (50 mg/L) within 20 h, at pH 8.0 and a wide range of temperatures (30–40 °C) under static conditions [ 12 ]. Pham et al (2022) investigated a novel member of the genus Bacillus —namely, Bacillus React3—which can degrade Methylene Blue (MB) during the production of the lignin peroxidase enzyme [ 11 ].…”
Section: Introductionmentioning
confidence: 99%